TRP channels and breast cancer: the role of TRPs in the pathophysiological development - Zhang, Yu; Yi, Yanfeng; Shu, Yinghao; Ru, Xiaochen; He, Shuaibing (Frontiers in Molecular Biosciences, 2025)
TRP channels play important roles in regulating various physiological and pathological processes, including the progression of cancer. Several TRP channels mediate tumour development. This review focuses on the role of TRP channels in the development of breast cancer, including their involvement in proliferation, apoptosis, autophagy, metastasis, and angiogenesis. TRP channels are associated with breast carcinogenesis and their role as potential therapeutic targets and prognostic biomarkers is under investigation. This review summarizes the reported effects of inhibiting or agonizing various TRP channel in breast cancer cells. Although there are relatively mature protocols for the treatment of breast cancer, its treatment is not currently a breakthrough, and therapies targeting TRP channels may be a developable strategy for it.